Identification of density and breeding places of Aedes mosquito and prevalence of dengue in Rajshahi city corporation of Bangladesh - Uddin, M. Helal; Islam, M. Nazmul; Islam, S. M. Shahinul; Aktaruzzaman, M. M.; Haque, M. Ekramul; Habiba, M. Umme; Rakibuzzaman, M.; Hamid, M. Rahul; Rashid, Sumya Binty; Bari, M. Abdul (International Journal of Research in Medical Sciences, 2023)
Background: There are various varieties of habitats that have specific characteristics of water for the breeding of mosquito. A house-to-house cross-sectional entomological survey used to be carried out at per domestic area to become aware of larval breeding sites. Aedes aeygypti used to be primary vector and Aedes albopictus used to be predominant species in container-breeding habitats. Most breeding habitats have been category into excessive stage of larval density. Turbidity, pH, TOC, magnesium, calcium and sodium is amongst the characteristics that indicates a significant difference with larval density and species composition respectively. This study personal based entomological research and funding carried out by corresponding author. Students of zoology department of Rajshahi university involved in this research. Students were working as a research assistant for this study. Aim of this study was to assess determination of prevalence, density and breeding place of Aedes mosquito in Rajshahi city corporation. Methods: This observational study carried out 30 wards in Rajshahi city corporation areas have been surveyed in department of communicable diseases control, director general of health services, Dhaka, Bangladesh. Duration of study 3 years. Total 3 surveys were conducted in each year; pre monsoon, monsoon and post monsoon total 9 surveys conducted by this 3 years survey period. Data entered in MS excel and statistical analysis done by SPSS trial version. Results: This study shows that according to breeding area of 2020-2022. Here, total surveyed household were 8100. Total positive Wet container were 474 and positive place were 473 in these three years survey. Conclusions: Aedes aegypti and Aedes albopictus are properly established inside urban places. Meteorological variables additionally affected mosquito populations. Characteristics of mosquito breeding area can affect larval density and give impact quality of life.